2023
DOI: 10.1103/physrevb.107.245413
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and optical properties of superlattices of epitaxially connected nanocrystals

Abstract: Colloidal semiconductor nanocrystals (NCs) are believed to strongly absorb resonant light; this property is key to ongoing applications of NCs as phosphor in light-emitting diodes (LEDs) for lighting, in displays, and photodetectors. However, it has been realized that NCs in a low dielectric medium suffer from a weak permeation of the electromagnetic field in the solid due to formation of depolarization fields, strongly reducing light absorption, as quantified by the local-field factor. For low-dimensional sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Superlattices represent a distinct category of materials with periodic structures, potentially exhibiting unique properties such as dielectric, 1 optical, 1−4 magneto-optical, 5 electrical, 6 mechanical, 7 and gas-sensing characteristics. 8 Within the realm of nanoscale self-assembly, the investigation of nanopolyhedron-based superlattices has been a subject of comprehensive research, both experimentally and theoretically, spanning several decades.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superlattices represent a distinct category of materials with periodic structures, potentially exhibiting unique properties such as dielectric, 1 optical, 1−4 magneto-optical, 5 electrical, 6 mechanical, 7 and gas-sensing characteristics. 8 Within the realm of nanoscale self-assembly, the investigation of nanopolyhedron-based superlattices has been a subject of comprehensive research, both experimentally and theoretically, spanning several decades.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Superlattices represent a distinct category of materials with periodic structures, potentially exhibiting unique properties such as dielectric, optical, magneto-optical, electrical, mechanical, and gas-sensing characteristics . Within the realm of nanoscale self-assembly, the investigation of nanopolyhedron-based superlattices has been a subject of comprehensive research, both experimentally and theoretically, spanning several decades. Prior research has predominantly centered on superlattices assembled using non-octahedral building blocks, , such as nanocubes, which typically adopt simple cubic structures. However, employing nano-octahedra as the assembly building blocks presents a compelling deviation. , For instance, Zhu et al observed a fascinating monolayer arrangement comprising 70 nm gold nano-octahedra, while Gong et al confirmed the presence of simple hexagonal and monoclinic (reconstructed as triclinic in this work) superstructures of gold nano-octahedron self-assemblies via a scanning electron microscopy technique.…”
Section: Introductionmentioning
confidence: 99%